2019
DOI: 10.1177/1077559519848489
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Services to Reduce Child Sexual Abuse Recurrence

Abstract: Child sexual abuse (CSA) is associated with a range of negative consequences for victims that are compounded when it recurs. We used the National Child Abuse and Neglect Data System to study a cohort of 42,036 children in 45 U.S. states with sexual abuse reports first confirmed by child protective services (CPS) during 2010 in order to identify children with increased risk for recurrence. A small proportion (3.6%) had a second confirmed sexual abuse report through 2015. In multivariate models, female gender, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…Victim sex was an independent predictor of each type of revictimization, with moderate effect sizes; sexually abused girls were at heightened risk for sexual revictimization, whereas sexually abused boys were at heightened risk for both violence and non-violence revictimization. This is consistent with the evidence base on risk factors for sexual and violent victimization in general, as well as with studies examining predictors of revictimization following abuse (DeCamp & Zaykowski, 2015; Palusci & Ilardi, 2019; Pittenger et al, 2018). It is possible that the magnitude of the difference between abused males and females in rates of sexual revictimizationis influenced by males disclosing experiences of sexual assault less frequently than females, perhaps due to concerns of being labeled homosexual, masculine ideals of self-reliance, erroneous assumptions that such experiences are a normative part of boys’ lives, and expectations that others may minimize their experiences (Alaggia, 2004; Pittenger et al, 2018; Spataro et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Victim sex was an independent predictor of each type of revictimization, with moderate effect sizes; sexually abused girls were at heightened risk for sexual revictimization, whereas sexually abused boys were at heightened risk for both violence and non-violence revictimization. This is consistent with the evidence base on risk factors for sexual and violent victimization in general, as well as with studies examining predictors of revictimization following abuse (DeCamp & Zaykowski, 2015; Palusci & Ilardi, 2019; Pittenger et al, 2018). It is possible that the magnitude of the difference between abused males and females in rates of sexual revictimizationis influenced by males disclosing experiences of sexual assault less frequently than females, perhaps due to concerns of being labeled homosexual, masculine ideals of self-reliance, erroneous assumptions that such experiences are a normative part of boys’ lives, and expectations that others may minimize their experiences (Alaggia, 2004; Pittenger et al, 2018; Spataro et al, 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have found that individuals experiencing sexual revictimization report being younger at the time of their initial sexual abuse compared to individuals not revictimized (Casey & Nurius, 2005; Jenkins et al, 2018; Pittenger et al, 2018). Others have shown that CSA occurring during adolescence is associated with increased risk of revictimization (Humphrey & White, 2000; Palusci & Ilardi, 2019; Siegel & Williams, 2003), and others still have found no effect of age (Jankowski et al, 2002; Maker et al, 2001). Previous research has also found that indicators of initial abuse severity (e.g., more invasive, frequent, and chronic abuse, the use of force, an intra-familial perpetrator) are related to revictimization both during adolescence and adulthood (e.g., Casey & Nurius, 2005; Fortier et al, 2009; Humphrey & White, 2000; Matta Oshima et al, 2014; Simmel et al, 2012; Swanston et al, 2002).…”
mentioning
confidence: 99%
“…Additionally, findings were mixed or inconclusive regarding select characteristics of the child, family, and community/social systems. 20,22 • Sexual and high-risk behavior 17 • Gender 20,23 Mixed or inconclusive findings • Age 20,22,23 • Race and ethnicity 20,23,24 • Disability 22-24 Characteristics of the maltreatment Risk factors • Perpetrator being the mother's significant other or the victim's babysitter 18 • The sexual abuse occurring in a familiar place 18 • Prior emotional abuse 16 • Severity of initial sexual abuse 16,25 Family Risk factors…”
Section: Resultsmentioning
confidence: 99%
“…• Parent history of sexual abuse or mental health concerns 22 • Domestic violence 20,22,23 • Family hearing and vision problems 23 • The presence of a non-caregiver adult in the house 20 • Changes in the child's caregivers 16 Protective factors • Identified family social supports 22 • Parent believing the child's initial victimization occurred 22 Mixed or inconclusive findings • Family substance abuse 22,23 • Family socioeconomic status 22,24 Community/social systems Risk factors • Active or prior child welfare involvement 17,22 • Prior law enforcement involvement 22 • Receiving mental health treatment 20 Mixed or inconclusive findings • Neighborhood socioeconomic status 20,26 • Services received from Child Protective Services 23,24…”
Section: Resultsmentioning
confidence: 99%
“…Like the field, my early work looked at medical and forensic issues in physical and sexual abuse, but I now use epidemiology and administrative data to study diagnosis, reporting, recurrence, fatality, and prevention (American Professional Society on the Abuse of Children, 2010; Bearup & Palusci, 1999; Greiner et al, 2013; Kennedy et al, 2020; Palusci et al, 2019; Palusci et al, 2001; Palusci & Ilardi, 2020; Palusci & Ondersma, 2012; Palusci & Reeves, 2003; Palusci et al, 2016; Roygardner et al, 2020). We will also need to pay attention to new technology and other emerging areas (Siegel & Palusci, 2019).…”
Section: Where We May Gomentioning
confidence: 99%